Strategi Optimal Peletakan Titik Pembuangan Sampah di Tepian Sungai Musi Kelurahan 3-4 Ulu - Ahmad Faqih Sadewa; Lulu Farahdina; Muhammad Charvian Faiz; Nisrina Fedora Apsarini (Archvisual: Jurnal Arsitektur dan Perencanaan, 2024)
The problem of waste in dense settlements on river banks is one of the problems that has not been resolved to date. The increase in the amount of waste is not accompanied by the land area available for waste facilities and infrastructure, resulting in deviations in handling waste by dumping it into rivers. Proper handling of this problem can reduce the impact that occurs. One of the sub-districts in Palembang City facing this problem is Sub-district 3-4 Ulu, which directly borders The Musi River and densely populated settlements right on the banks of The Musi River. The methods used in this research are observation, interviews, and questionnaires to obtain data. The analytical methods used are descriptive analysis methods and superimpose analysis. The descriptive analysis method explains the characteristics of the community, while the superimpose analysis method provides options for placing appropriate waste disposal points. Then, information was obtained regarding the habits of the riverside residents of 3-4 Ulu Village in disposing of rubbish and the practical solutions for dealing with the rubbish problem.